2009
DOI: 10.1080/13625180802379964
|View full text |Cite
|
Sign up to set email alerts
|

Does readily available emergency contraception increase women's awareness and use?

Abstract: Among women seeking termination of pregnancy wider availability of the ECP has increased women's awareness of EC but not use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
(26 reference statements)
1
14
1
Order By: Relevance
“…This is higher than the 24.5% reported among Egyptian women aged 18-49 years [14]. The higher prevalence of ECP use in this study as compared to others studies [18, 19, 31] could be due to the fact that a large proportion of the women said ECPs were available (92.0%) and affordable (87.7%). Further confirming our findings, our univariate and multivariate logistic regression analysis indicated that participants who said ECPs were available and affordable were more likely to use them as compared to those who said it was not.…”
Section: Discussioncontrasting
confidence: 75%
“…This is higher than the 24.5% reported among Egyptian women aged 18-49 years [14]. The higher prevalence of ECP use in this study as compared to others studies [18, 19, 31] could be due to the fact that a large proportion of the women said ECPs were available (92.0%) and affordable (87.7%). Further confirming our findings, our univariate and multivariate logistic regression analysis indicated that participants who said ECPs were available and affordable were more likely to use them as compared to those who said it was not.…”
Section: Discussioncontrasting
confidence: 75%
“…Although Australian women have a high level of awareness of the ECP, their knowledge about how and when to use it and where to obtain it is inadequate, thus increasing their risk of becoming pregnant 9 . These findings confirm international findings, which reveal that increased awareness of the ECP neither affects its actual use 10 nor reduces rates of unplanned pregnancy 11 . There is a gap between women's broader awareness of emergency contraception and contraception in general versus their specific knowledge and subsequent utilisation of emergency contraception.…”
Section: Knowledge Of Emergency Contraception and The Ecpsupporting
confidence: 69%
“…37 Improved availability and access to levonorgestrel were found to lead to increased patient awareness of emergency contraception, but this did not translate into increased use. 38 Given the results of these studies from three different countries, [35][36][37][38] an OTC designation for oral contraceptives may improve women's access to and, in some cases, use of oral contraceptives while also raising their awareness of other options for contraception.…”
Section: Policy Issue Considerationsmentioning
confidence: 99%